Healthcare Resource Consumption and Related Costs of Patients Estimated with Treatment-Resistant Depression in Italy - Perrone V; Sangiorgi D; Andretta M; Ducci G; Forti B; Francesa Morel PC; Gambera M; Maina G; Mencacci C; Mennini FS; Zanalda E; Degli Esposti L (ClinicoEconomics and Outcomes Research, 2021)
Valentina Perrone,1 Diego Sangiorgi,1 Margherita Andretta,2 Giuseppe Ducci,3 Bruno Forti,4 Pier Cesare Francesa Morel,5 Marco Gambera,6 Giuseppe Maina,7 Claudio Mencacci,8 Francesco Saverio Mennini,9,10 Enrico Zanalda,11 Luca Degli Esposti1 1CliCon S.r.l., Health, Economics & Outcomes Research, Bologna, Italy; 2UOC Assistenza Farmaceutica Territoriale, Azienda ULSS 8 Berica, Vicenza, Italy; 3Mental Health Department, ASL Roma 1, Rome, Italy; 4Mental Health Department - Azienda ULSS n 1 “Dolomiti”, Veneto Region, Italy; 5Janssen-Cilag SpA, Milano, Italy; 6“OSPEDALE P. PEDERZOLI” Casa di Cura Privata S.p.A., Peschiera del Garda, Verona, Italy; 7Department of Neuroscience “Rita Levi Montalcini”, University of Turin, University Hospital San Luigi Gonzaga, Turin, Italy; 8Department of Neuroscience, ASST Fatebenefratelli Sacco, Milan, Italy; 9EEHTA - CEIS (Centre for Economic and International Studies), Faculty of Economics, University of Rome “Tor Vergata”, Rome, Italy; 10Institute for Leadership and Management in Health Care, Kingston University, London, UK; 11Department of Mental Health ASL TO3 & AOU San Luigi Gonzaga, Collegno, TO, ItalyCorrespondence: Valentina PerroneCliCon S.r.l. Health, Economics & Outcomes Research, via Murri, 9, Bologna, 40137, ItalyTel +39 0544 38393Fax +39 0544 212699Email valentina.perrone@clicon.itPurpose: To analyse the healthcare resource consumption and related costs for the Italian National Health System of patients estimated to be affected by treatment-resistant depression (TRD) in Italy.Patients and Methods: This was an observational retrospective study based on administrative databases, including those related to residential/semiresidential structures, of Veneto Region and the Local Health Unit of Bergamo in Italy (for a total of around 6 million health-assisted subjects). Between July 2011 and December 2017, all adult patients with a third antidepressant (AD) after ≥ 2 AD (each one with at least ≥ 4 weeks duration, ≥ 1 prescription at maximum dosage reported in datasheets, a grace period ≤ 30 days when switching AD and treatment maintained ≥ 9 months) were included. Overall and psychiatry-related healthcare resources consumption and related costs were estimated on a 12-months based analysis. Data were re-proportioned to the Italian population.Results: We have previously estimated a total of 101,455 patients with TRD in Italy (130,049 considering the mean maximum dosage of AD). Of them, 44.2% had at least a psychiatric hospitalization/visit or accessed a residential/semiresidential structure, and 31% added another AD or a mood stabilizer/antipsychotic drug. Patients with at least one psychiatry-related hospitalization increased over the number of antidepressant lines from 12.0% during first line up to 24.5% during fourth line. Direct healthcare costs increased from € 4,405 for first line to € 9,251 from fifth line onwards. Psychiatry-related costs went from € 1,817 (first line) to € 4,606 (fifth line onwards) and were mainly driven by residential/semiresidential structures and hospitalizations.Conclusion: An upward trend with number of AD lines was observed for all healthcare resource utilization and consequently for all direct costs, thus indicating an increasing burden for patients as they move forward AD lines.Keywords: depression, healthcare costs, real-world, TRD